Fetal Rhabdomyoma of the Right Tonsil with Polyp-Like Appearance - Ching-Ping Wang; Yi-Hao Chang; Ya-Ting Chang (Case Reports in Otolaryngology)
Skeletal muscle neoplasms, in contrast to other groups of tumors, are almost malignant. The benign variant, rhabdomyoma, is distinctly rare. Rhabdomyomas can be classified generally into two types: cardiac and extracardiac. Extracardiac rhabdomyoma can be further divided into three subtypes: adult, fetal, and genital type. Adult rhabdomyoma is the most common subtype of rhabdomyoma even though it remains relatively rare. Fetal rhabdomyomas are less common than the adult type. In this paper we report a rare case of a fetal rhabdomyoma with polyp-like appearance originating from right tonsil. Punch biopsy and then right tonsillectomy were performed for complete excision. There was no obvious recurrence.